Man vs. Machine: A Comparative Study of AI and Human-Generated Narratives - Esha Munir; Dr. Zahida Hussain; Shama Fatima (Indus Journal of Social Sciences, 2025)
The research aims to show that AI systems can create human like narratives that resonate and captivate the readers and how they are different from the human narratives. Artificial Intelligence (AI) is the imitation of cognitive ability in the devices that act or think like humans. It performs various tasks like reasoning, problem solving, learning, language understanding and perception based on human intelligence. As the world becomes more digitalized, AI will appear as the backbone of progressive education, making learning more accessible, adoptive, and cognitive. With developments like Meta AI, educational situations will become more interactive, immersive, and designed to individual learning styles. The research analyzes the two short stories, a human generated story A Very Old Man with Enormous Wings by Gabriel Garcia Marquez and AI generated story The Island of the Forgotten Musician by using the framework of Austin and Searle’s Speech Act Theory. J. L. Austin and Searle examine that language is not only used to present reality but at the same time it also performs some actions. Use of utterances within the stories violates the rules of Speech Act Theory. By using this theory, the research identifies the language used to convey meanings, create social relationships between the characters and the similarities and differences between the man created story and AI generated story. AI has a natural language process (NLP) that helps the devices to understand human language and to solve their queries. The research is qualitative in nature and the texts of the stories are used as primary data.